2015
DOI: 10.4236/ce.2015.612123
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Factor Analysis on Generating Teaching and Learning Guiding Principles from Malaysian Teacher Educators’ Perspectives

Abstract: The purpose of this study was to develop and establish the validity and reliability of Teaching and Learning instrument to generate teaching and learning guiding principles. Participants consisted of 171 Malaysian teacher educators. The Teaching and Learning instrument is a 5-point Likertscaled survey consisting of 67 statements and 6 subscales. The internal consistency using Cronbach's coefficient alpha for every subscale is greater than 0.700. For the overall instrument using the 67 items that comprised the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…The "guiding principles for teaching and learning" were developed at the start of the NRGS via document review of present policy positions, as well as expert interviews with policymakers and experts in teacher education. "A Teaching & Learning Checklist" was produced, piloted, and validated using exploratory factor analysis based on the "guiding principles for teaching and learning", confirming the six-factor checklist [36] with 67 initial items reduced to 50. The "Guiding Principles for Teaching and Learning" show the intended or aspired teaching practices in teacher preparation program, but the actual or direct implementation of science-based teaching practices still has to be determined via classroom observations.…”
Section: Instrumentationmentioning
confidence: 78%
See 1 more Smart Citation
“…The "guiding principles for teaching and learning" were developed at the start of the NRGS via document review of present policy positions, as well as expert interviews with policymakers and experts in teacher education. "A Teaching & Learning Checklist" was produced, piloted, and validated using exploratory factor analysis based on the "guiding principles for teaching and learning", confirming the six-factor checklist [36] with 67 initial items reduced to 50. The "Guiding Principles for Teaching and Learning" show the intended or aspired teaching practices in teacher preparation program, but the actual or direct implementation of science-based teaching practices still has to be determined via classroom observations.…”
Section: Instrumentationmentioning
confidence: 78%
“…The non-participatory observation strategy was chosen since it was more impartial to hone our focus on the chemistry teaching strategies that were being implemented. The teaching and learning regulatory principles were earlier designed, authenticated, outlined and reported in [36], [37]. The observation checklist named as the "Teaching and Learning Guiding Principles" has items that are divided into six practices or key points.…”
Section: Research Methods 31 Research Designmentioning
confidence: 99%
“…The comparison between the previous study about the TLGP and this study is as shown in Table 2. Table 2 Comparision of Previous and Present Study of Teaching and Learning Guiding Principles (TLGP) Previous study (Adnan et al, 2015) This study Reason…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this article is to present the processes and analyses involved in further validating the Teaching and Learning Guiding Principles (TLGP) in the context of higher learning institutions in Malaysia by Adnan, Masuwai, Tajudin, & Rahman (2015). The previous stage of the research resulted in six key themes, later labeled as constructs, related to principles of teaching and learning.…”
Section: Background Of the Researchmentioning
confidence: 99%
See 1 more Smart Citation